Treatment Patterns and Survival of Patients With Advanced Non-Small Cell Lung Cancer Guided by Comprehensive Genomic Profiling: Real-World Single-Institute Study in China - Lv, Weize; Cheng, Hua; Shao, Di; Wei, Yajun; Zhu, Weiping; Wu, Kui; Jiang, Wenxi; Hu, Liyang; Sha, Zhou; Zhong, Beilong; Pei, Xiaofeng (Frontiers in Oncology, 2021)
Although the National Comprehensive Cancer Network and the Chinese Society of Clinical Oncology guidelines recommend comprehensive genomic profiling of lung adenocarcinoma, it has not been widely applied in Chinese hospitals. This observational study aimed to determine real-world evidence of whether comprehensive genomic profiling can benefit the survival of patients with lung cancer. We investigated the frequency of genomic alterations, treatment strategies, and clinical outcomes in 233 patients with advanced non-small cell lung carcinoma who were routinely screened using a 508-gene panel. The most prevalent drivers were mutations of EGFR (51%), KRAS (9%), PIK3CA (7%), ALK (7%), MET (6%), and BRAF (5%). Mutations in tumor suppressor genes included TP53, KEAP1, RB1, PTEN, and APC. Median overall survival (OS) was significantly shorter among patients harboring KRAS (mutant, n = 17; WT, n = 154) and TP53 (mutant, n = 103; WT n =68) mutations (11.3 vs. 24.0 months; P = 0.16 and 18.7 vs. 28.7 months; P = 0.018, respectively). The OS was longer among patients with tumors harboring EGFR (P = 0.069) and ALK (P = 0.51) mutations. Most patients (65.4%) with the driver gene-positive (EGFR, ALK, and ROS1) tumors were received TKI treatment, whereas those with driver gene wild tumors (53.1%) chose platinum-based therapy. Univariate and multivariate analyses associated a shorter OS among patients with tumors harboring concomitant TP53 and EGFR mutations. These findings provide additional evidence from real-world on the potential importance of targeted therapies as a treatment option in NSCLC patients harboring clinically actionable mutation.